An Experimental Insight into Extracellular Phosphatases – Differential Induction of Cell-Specific Activity in Green Algae Cultured under Various Phosphorus Conditions - Vrba, Jaroslav; Macholdová, Markéta; Nedbalová, Linda; Nedoma, Jiří; Šorf, Michal (Frontiers in Microbiology, 2018)
Extracellular phosphatase activity (PA) has been used as an overall indicator of P depletion in lake phytoplankton. However, detailed insights into the mechanisms of PA regulation are still limited, especially in the case of acid phosphatases. The novel substrate ELF97 phosphate allows for tagging PA on single cells in an epifluorescence microscope. This fluorescence labeled enzyme activity (FLEA) assay enables for autecological studies in natural phytoplankton and algal cultures. We combined the FLEA assay with image analysis to measure cell-specific acid PA in two closely related species of the genus Coccomyxa (Trebouxiophyceae, Chlorophyta) isolated from two acidic lakes with distinct P availability. The strains were cultured in a mineral medium supplied with organic (beta-glycerol phosphate) or inorganic (orthophosphate) P at three concentrations. Both strains responded to experimental conditions in a similar way, suggesting that acid extracellular phosphatases were regulated irrespectively of the origin and history of the strains. We found an increase in cell-specific PA at low P concentration and the cultures grown with organic P produced significantly higher (ca. tenfold) PA than those cultured with the same concentrations of inorganic P. The cell-specific PA measured in the cultures grown with the lowest organic P concentration roughly corresponded to those of the original Coccomyxa population from an acidic lake with impaired P availability. The ability of Coccomyxa strains to produce extracellular phosphatases, together with tolerance for both low pH and metals can be one of the factors enabling the dominance of the genus in extreme conditions of acidic lakes. The analysis of frequency distribution of the single-cell PA documented that simple visual counting of ‘active’ (labeled) and ‘non-active’ (non-labeled) cells can lead to biased conclusions regarding algal P status because the actual PA of the ‘active’ cells can vary from negligible to very high values. The FLEA assay using image cytometry offers a strong tool in plankton ecology for exploring P metabolism.